Chapter Internet - Romano, Antonello (Strumenti per la didattica e la ricerca, 2022)
The pre-requisite of the Platform Society is the 'digital': Internet accessibility and connection speed become determining factors for platforms and users. However, the International Telecommunication Union data confirm that the possibility of Internet connection remains profoundly uneven.